Peningkatan Keaktifan Siswa Dan Minat Belajar Pada Pembelajaran PKn Melalui Stratagi Question Student Have Pada Kelas III SD Muhammadiyah 10 Tipes Surakarta Tahun Ajaran 2015 / 2016 - ARIANI PRAMEND, ASRI (2016)
The purpose of this research is increase liveliness students and learning interest in the learning pkn using the strategies student have question .In research the act of this class subject beneficiary of the action was the third grade amounting to 32 students, the subject of actors of the researchers and teachers. Engineering data collection by using the method interview, observation, and documentation. In this research analysis techniques the data used was descriptive statistics. The analysis cycle meeting on I ke-1 liveliness students 73,44 % ( 23 students from 32 students ) and interest learn from students at 72,65 % ( 22 students from 32 students ). On the cycle I meeting ke-2 liveliness students became 74,21 % ( 24 students from 32 students ) while interest learn 78,90 % ( 25 students from 32 students ). On the cycle II meeting ke-1 increased liveliness students became 75,78 % ( 25 students from 32 students ) while interest study to be 75,78 % ( 25 students from 32 students ). On the cycle II meeting ke-2 liveliness students became 82,03 % ( 26 students from 21 students ) and interest learn 85,15 % ( 27 students from 32 students ). Concluded that learning using the strategies question student have to increase liveliness students and interest learn from learning PKn on the kids third grade Primary Muhammadiyah 10 Tipes Surakarta 2015 / 2016.